2017
DOI: 10.1038/ncomms14569
|View full text |Cite
|
Sign up to set email alerts
|

Breather soliton dynamics in microresonators

Abstract: The generation of temporal cavity solitons in microresonators results in coherent low-noise optical frequency combs that are critical for applications in spectroscopy, astronomy, navigation or telecommunications. Breather solitons also form an important part of many different classes of nonlinear wave systems, manifesting themselves as a localized temporal structure that exhibits oscillatory behaviour. To date, the dynamics of breather solitons in microresonators remains largely unexplored, and its experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
105
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(110 citation statements)
references
References 36 publications
2
105
1
Order By: Relevance
“…This scenario is similar to the one regarding bright solitons in the anomalous dispersion regime [12,13]. In the anomalous dispersion regime, such temporal oscillations, also called "breathers", were experimentally first observed in fiber resonators [12] and have recently also been measured in microresonators [48][49][50]. In the anomalous regime, it was furthermore shown that TOD, which leads to drift instabilities, could suppress such oscillatory and chaotic temporal dynamics of bright solitons [26,27].…”
Section: Suppression Of Temporal Soliton Instabilitiesmentioning
confidence: 57%
“…This scenario is similar to the one regarding bright solitons in the anomalous dispersion regime [12,13]. In the anomalous dispersion regime, such temporal oscillations, also called "breathers", were experimentally first observed in fiber resonators [12] and have recently also been measured in microresonators [48][49][50]. In the anomalous regime, it was furthermore shown that TOD, which leads to drift instabilities, could suppress such oscillatory and chaotic temporal dynamics of bright solitons [26,27].…”
Section: Suppression Of Temporal Soliton Instabilitiesmentioning
confidence: 57%
“…However, Metallic 1T MoS2 has been confirmed as a superior supercapacitor electrode material [6]. Furthermore, a series of 1T-type 2D TMDs have also been reported to have in-plane negative Poisson's ratio due to the strong coupling between different electronic orbits [7]. Even though 1T phase is less stable than 2H, 1T TMDs have been experimentally synthesized [8] [9] and have many exotic novel properties [1][7] [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dissipative solitons are self-enforcing, stationary structures that exist in diverse nonlinear dissipative systems subject to an external pump of energy 1 . The recent discovery of temporal dissipative solitons in optical cavities displaying Kerr nonlinearity 2,3 (from now on dissipative Kerr solitons or DKS) has facilitated the investigation of their rich dynamics [4][5][6][7][8][9][10][11][12][13][14][15] . DKS rely on balancing the inherent cavity dispersion with the corresponding Kerr nonlinear phase shift induced by the soliton, while the dissipative nature of the microresonator is offset by supplying the cavity with the energy from a pump laser.…”
mentioning
confidence: 99%